STUDENTS’ PERCEPTION TOWARD WRITING DESCRIPTIVE TEXT USING NOREDINK WEBSITE - Santi Aprillia Rahayu (PROJECT (Professional Journal of English Education), 2023)
The purpose of this research is to observe students’ perception in writing descriptive text using the NoRedInk website. Writing is one skill that can help students develop their critical thinking in written form. The students can express their feeling, ideas, or think into readable text which can be understood by the reader. The method that applied in this research is descriptive qualitative method research by a survey approach through the questionnaire. The sample of this research ere 30 students from one class which is the nursing department of X at SMK Tunas Mekar Rancaekek. The data of this research was gained with 10 questions of the questionnaire. The objective of this research is to observe students’ perception in writing descriptive using the NoRedInk website. Based on the result of the data that has been analyzed, the researcher concludes that the student's writing skill in descriptive text using the NoRedInk website was positive. The students mostly knew that they have skills in wiring descriptive text. Based on the questionnaire, the teacher and the media are good for descriptive text. The students give positive responses about the media, and the teacher has a good system to deliver the material of the descriptive text. Keywords:  Students’ Perception; Descriptive Text; NoRedInk Website